Evaluation of common indoor air pollutant reduction by a botanical indoor air biofilter system. Issue 1 (January 2021) - Ibrahim, Izdihar Zahirah; Chong, Wen Tong; Yusoff, Sumiani; Wang, Chin-Tsan; Xiang, Xianbo; Muzammil, Wan Khairul
Indoor air pollutant issues have attracted various researchers to investigate alternative solutions to non-biofiltration systems, such as common air purifiers that are generally used in the market. Research has found that active botanical biofilter systems are efficient in filtering indoor air pollutants, as well as providing a refreshing environment to surroundings. The research presented here describes a developed prototype of a botanical indoor air biofilter (BIAB) and evaluates the performance of the BIAB system in reducing common indoor air pollutants. The system was assessed for its single-pass filtration across an aerosol containing particles with the diameter of 2.5 µm (PM2.5 ), 10 µm (PM10 ) and volatile organic compounds (VOCs) by burning aromatic cone incense. The system comprises three working sections: a fraction of horizontally grown plants with growth media as the botanical biofiltration section, an evaporative medium (an additional component from a commercial active botanical biofilter) and a mechanical ventilation system that supplies cleaned air to the surroundings. The BIAB system recorded the removal efficiencies of 54.5 ± 6.04% for PM2.5, 65.42 ± 9.27% for PM10 and 46 ± 4.02% for VOCs.